UMP strengthens bilateral ties with UoS - Shariza, Mat Aris
Universiti Malaysia Pahang (UMP)’s Centre of Earth Resources and Research Management (CERRM) organised a research trip to University of Seoul (UoS), South Korea on April 20, 2012.